The Relationship Between Anxiety Levels and Asthma Recurrences in Adult Asthma Patients in the Koto Baru Dharmasraya Community Health Center Work Area in 2025 - costarin (Journal of health research and technology, 2025)
The World Health Organization (WHO) indicates that the prevalence of asthma continues to increase, with 335 million people worldwide suffering from this condition by 2023, and asthma contributing to 15% of global deaths.Based on data from the Koto Baru Community Health Center, data on the number of asthma sufferers in 2024 showed an increase in asthma sufferers, namely around 62 people consisting of 30 children and 32 adults. The purpose of this study was to determine the relationship between anxiety levels and asthma relapses in adult asthma sufferers. This research method is descriptive correlation with a cross-sectional study approach, with a population of 62 asthma sufferers consisting of 30 children and 32 adults. The sampling technique was total sampling, with a sample of 32 adult asthma sufferers. Bivariate analysis used a correlation test. The results of this study showed that respondents who had moderate anxiety levels were 50% and those who experienced moderate asthma relapses were 56%. The statistical test results indicate a relationship between anxiety levels and asthma relapses in adult asthmatics (p-value 0.037 <0.05). This study is expected to contribute scientific insight to healthcare professionals and serve as an additional new reference for the Koto Baru Community Health Center. Keywords: Anxiety, Asthma Relapse